Safety and efficacy of Levucell SC® (Saccharomyces cerevisiae CNCM I‐1077) as a feed additive for calves and minor ruminant species and camelids at the same developmental stage. (12th June 2019) - ,; Bampidis, Vasileios; Azimonti, Giovanna; de Lourdes Bastos, Maria; Christensen, Henrik; Dusemund, Birgit; Kouba, Maryline; Kos Durjava, Mojca; López‐Alonso, Marta; López Puente, Secundino; Marcon, Francesca; Mayo, Baltasar; et al.
Abstract: Following a request from the European Commission, the EFSA Panel on Additives and Products or Substances used in Animal Feed was asked to deliver a scientific opinion on the safety and efficacy of Levucell ® SC when used in feed for calves and minor ruminant species and camelids at the same developmental stage. The additive consists of viable cells of Saccharomyces cerevisiae . This species is considered by EFSA to be suitable for the Qualified Presumption of Safety (QPS) approach to safety assessment. This approach requires the identity of the strain to be conclusively established. The strain was found to meet the criteria for the QPS approach in the context of previous opinions and since concerns are not expected from other components of the additive, Levucell ® SC is presumed safe for all target species, consumers of products derived from animals fed the additive and for the environment. The Panel considers these conclusions to apply also in the current assessment. In a previous opinion, the Panel also concluded that the additive is considered an eye irritant but not a dermal irritant or sensitiser and that inhalation exposure is unlikely. Since the use of the additive in calves and minor ruminant species and camelids at the same developmental stage is considered unlikely to introduce hazards for users of the product not already considered as part of the first assessment, these conclusions are still considered valid. Levucell SC ® has the potential to be efficacious in calves at the minimum inclusion level of 1 × 10 9 CFU/kg complete feed. The conclusion on efficacy for calves can be extrapolated to minor ruminant species and camelids at the same developmental stage.